2001
DOI: 10.1039/b103427h
|View full text |Cite
|
Sign up to set email alerts
|

Ionic columnar metallomesogens formed by three-coordinated copper(I) complexes

Abstract: Two series of copper() complexes (1, 2) derived from bis{2-[3Ј-(3Љ,4Љ-dialkoxyphenyl)-5Ј-methyl-1Ј-pyrazolyl]ethyl} ethers and from bis{2-[3Ј-(3Љ,4Љ,5Ј-trialkoxyphenyl)-5Ј-methyl-1Ј-pyrazolyl]ethyl} ethers were prepared and characterized. These ionic copper() complexes were obtained by reaction of the ethers with [Cu(MeCN) 4 ]BF 4 in refluxing acetonitrile. All three-coordinated copper() complexes isolated as off-white solids were characterized by NMR spectroscopy and elemental analysis, and their mesomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A trinuclear Au(I) pyrazole-based complex 6 bearing long alkyl chains has been prepared and its solution in hexane was found to form a red-luminescent organogel (l em ¼640, l ext ¼284 nm) for an application of reversible RGB color switching. In contrast, known metallomesogens derived from pyrazoles were relatively scarce, some of the complexes incorporated with Ir/Rh(I/II), 7 Ni(II), 8 and Pd(II), 9 Cu(I/II), 10 Ag/Au(I), 11 and Zn(II) 12 ions were already reported. Columnar or smectic phases were obtained by rhodium(I) complexes derived from symmetrical or unsymmetric pyrazoles.…”
Section: Introductionmentioning
confidence: 81%
“…A trinuclear Au(I) pyrazole-based complex 6 bearing long alkyl chains has been prepared and its solution in hexane was found to form a red-luminescent organogel (l em ¼640, l ext ¼284 nm) for an application of reversible RGB color switching. In contrast, known metallomesogens derived from pyrazoles were relatively scarce, some of the complexes incorporated with Ir/Rh(I/II), 7 Ni(II), 8 and Pd(II), 9 Cu(I/II), 10 Ag/Au(I), 11 and Zn(II) 12 ions were already reported. Columnar or smectic phases were obtained by rhodium(I) complexes derived from symmetrical or unsymmetric pyrazoles.…”
Section: Introductionmentioning
confidence: 81%
“…These compounds usually have m.p.s higher than 100°C, and can be considered as high temperature ILs. = 12, 14, 16, 18 n = 10, 12, 14, 16, 18 Lin and Lai [67] reported the first time the mesomorphic tricoordinate Cu(I) complexes (74) with -N, -O donor of ethoxy bridged pyrazole moieties (Chart 13). Results from DSC, POM and XRD studies indicated the existence of hexagonal columnar phases in these complexes.…”
Section: Milcs Based On Imidazolesmentioning
confidence: 98%
“…The complex with [BF 4 ] À counter ion exhibited the widest temperature range of mesophase and lowest mesophase transition temperature.Piguet and co-workers [66] made extensive investigations to synthesize liquid crystalline lanthanide(III) complexes by using the mesomorphic ligands of the type L2-L4 (Scheme 2). Complexation of different lanthanides as [Ln(Lx)(NO 3 ) 3 ] (x = 1, 2 and 3 and Ln = Gd, Eu, Lu)(67)(68)(69) changed the conformation by interconversion of the I-shape and V-shape arrangements. The large Ln(NO 3 ) 3 core prevented mesomorphism in the complexes 67-69.These results demonstrated that mesogenic ligands do not always lead to metallomesogens upon complexation.…”
mentioning
confidence: 99%
“…12,13 Furthermore, copper is more abundant and is therefore a more affordable alternative to iridium or platinum complexes. With respect to liquid crystalline properties, very few copper(I) metallomesogens have been described and they show a broad structural diversity and varied ligands derived from tetrathiamacrocycles, 14 diiminobipyridine, 15 diiminopiridine, 16 alkylthiolate, 17 terpyridine, 18 isocyanide, [19][20][21][22] bis(pyrazolyl)ethyl ether, 23 phenanthroline, 24,25 pyrazolate, 26 phosphine, 27 thiolate, 28 benzoylthiourea 29 or biquinoline. 30 Moreover, the luminescent properties of copper(I) metallomesogens have hardly been analysed 26,27,30 and only two studies have reported quantum yield measurements, with the maximum values of up to 2.4% in the columnar phase 30 or 8% in the glassy smectic A phase.…”
Section: Introductionmentioning
confidence: 99%